Decision-Making Tools to Support Innovation: Guidelines and Case Studies - Galvez-Manriquez, D (wiley, 2023)
Scientific thinking concerning the way in which we drive innovation has been widely developed in recent years. It is known that the process of innovation consists of a succession of decision-making processes that require simultaneous technical, economical, organizational and sustainable compromises. Indeed, all innovative activities in business require stakeholders to seek out the best compromise between various, often contradictory dimensions of the same problems. Through studying practical cases from various fields (e.g. energy, marketing and sustainable development), this book addresses all the stages of the innovation process, highlighting some of the main decisions that can be faced by organizations. Based on the historical research conducted at the ERPI Laboratory (University of Lorraine) in Nancy, France, this book presents six innovation practices: strategy, creativity, design, project management, human resources and capitalization of knowledge. These practices are then illustrated through examples of decision support methods’ applications. © ISTE Ltd 2023.